2008
DOI: 10.1063/1.2913513
|View full text |Cite
|
Sign up to set email alerts
|

Substrate orientation effect on potential fluctuations in multiquantum wells of GaAs∕AlGaAs

Abstract: Suppression of nonradiative recombination process in directly Si-doped InAs/GaAs quantum dots J. Appl. Phys. 110, 103511 (2011) GaN directional couplers for integrated quantum photonics Appl. Phys. Lett. 99, 161119 (2011) Room temperature spin filtering effect in GaNAs: Role of hydrogen Appl. Phys. Lett. 99, 152109 (2011) Carrier localization and related photoluminescence in cubic AlGaN epilayers J. Appl. Phys. 110, 063517 (2011) Additional information on J. Appl. Phys. The photoluminescence ͑PL͒ t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…At low temperatures, excitons can be trapped into these fluctuations and, by increasing T L , they progressively diffuse and recombine radiatively from higher energy states [27]. By increasing the laser power density [26] the band-gap fluctuations are effectively screened reducing E p , as confirmed in Figs. 2(a), 2(b) and 2(c).…”
Section: A Interface Roughness Effectmentioning
confidence: 69%
See 3 more Smart Citations
“…At low temperatures, excitons can be trapped into these fluctuations and, by increasing T L , they progressively diffuse and recombine radiatively from higher energy states [27]. By increasing the laser power density [26] the band-gap fluctuations are effectively screened reducing E p , as confirmed in Figs. 2(a), 2(b) and 2(c).…”
Section: A Interface Roughness Effectmentioning
confidence: 69%
“…Here, p is a parameter related to the shape of the electron-phonon spectral function [24,26]. The deviation E p of the theoretical expectations and the experiment, is produced by local band-gap fluctuations provoked by interface roughness [26]. At low temperatures, excitons can be trapped into these fluctuations and, by increasing T L , they progressively diffuse and recombine radiatively from higher energy states [27].…”
Section: A Interface Roughness Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…12) Carrier localization is a lovely phenomenon in quantum well (QW) structures, which can be formed by the impurities, lattice disorder, layer thickness or composition variation. [13][14][15] In our recent study, 12) we showed that the presence of localized carriers could be ascribed to the energy potential modulation associated with the indium cluster formation and PZ field.…”
Section: Introductionmentioning
confidence: 93%